WILLIAM BLAKE- AN ENLIGHTENED VISIONARY - Mathur, Manisha (International Journal of Research -GRANTHAALAYAH, 2014)
William Blake an English painter poet and printmaker is considered as a seminal figure in the history of poetry and visual arts of the Romantic age. In the realm of imaginative painting Blake stands quite alone, and to find any real parallel to this extraordinary man of genius one must go back to the illuminators and sculptors of the twelfth century. Born out of time, with no tradition of imaginative painting to guide him, the intense flame if his genius burns fitfully blazing with an unbearable brilliance. Blake, for his idiosyncratic views is held in high regard by critics for his expressiveness and creativity, and for the philosophical and mystical undercurrents within his work. His paintings and poetry have been characterized as part of the Romantic movement are Pre-Romantic for its large appearance in the 18th C. Reverent of the bible but hostile to the Church of England, Blake was influenced by the ideals and ambitions of the French and American Revolutions.